Multimorbidities and quality of life in adult cerebral palsy over 40 years. - Dogruoz Karatekin, Bilinc; İcagasioglu, Afitap; Sahin, Seyma Nur; Akbulut, İsmail Hakan; Pasin, Ozge (My University, 2022)
This study aimed to describe the most common combinations of comorbidities and their relationship to quality of life in a sample of adults over 40 years of age with cerebral palsy.

Patients who are 40 years or older and admitted to the hospital in the last 5 years and were diagnosed with cerebral palsy were included. Demographic data and comorbidities were both questioned through the Patient Information Management System and confirmed by asking the individual about their diseases. The patients' quality of life was evaluated with the EQ-5D-3L Telephone interview version. Principal component analysis was used to determine comorbidity combinations for multiple morbidity.

Comorbidity was found in 72.1% of the participants and multimorbidity was found in 47.5%. The 5 most common comorbidities were musculoskeletal diseases (34.4%), psychiatric diseases (21.3%), essential hypertension (21.3%), osteoporosis (18%) and hyperlipidemia (18%). As a result of principal component analysis, a total of five components are formed and this most common comorbidity combinations in the sample explained 66.78% of the total variance.

New combinations of comorbidities have been demonstrated that may perhaps serve as a starting point for identifying new association of pathways. Future efforts are needed to identify modifiable factors for early intervention and prevention of chronic health problems in this population.
Keywords: Adult; Cerebral palsy; Comorbidity; Multimorbidity; Quality of life